2022
DOI: 10.1088/1361-665x/aca6bc
|View full text |Cite
|
Sign up to set email alerts
|

3D printed flexible wearable sensors based on triply periodic minimal surface structures for biomonitoring applications

Abstract: Soft piezoresistive wearable conductors have led to a paradigm shift in the monitoring of human bodily motions. Cellular additively manufactured conductors are promising piezoresistive components as they offer mechanical tunability and provide controllable percolation pathways. In the present study, we engineer high surface-area cellular structures with the triply periodic minimal surface (TPMS)-based architectures to tailor their piezoresistive response for use in wearable devices. A simple and economical fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In addition, a comparison of the sensing performance in terms of linearity, sensitivity, and linear range between the RLS sensor and other previously reported highly linear pressure sensors was conducted, as shown in Figure S23 and Table S1. Our sensor has achieved outstanding performance in ultra-broad linear pressure sensing, which, to the best of our knowledge, has not been previously reported and has been challenged. ,,,,, Furthermore, a comparison with other 3D printed flexible porous sensors was conducted and listed in Table S2, demonstrating its distinguishable characters with broad linear range, compact size, and without 3D model design. , …”
Section: Resultsmentioning
confidence: 86%
“…In addition, a comparison of the sensing performance in terms of linearity, sensitivity, and linear range between the RLS sensor and other previously reported highly linear pressure sensors was conducted, as shown in Figure S23 and Table S1. Our sensor has achieved outstanding performance in ultra-broad linear pressure sensing, which, to the best of our knowledge, has not been previously reported and has been challenged. ,,,,, Furthermore, a comparison with other 3D printed flexible porous sensors was conducted and listed in Table S2, demonstrating its distinguishable characters with broad linear range, compact size, and without 3D model design. , …”
Section: Resultsmentioning
confidence: 86%
“…In addition, the sensors with TPMS structure exhibit higher resilience than those with bulk structure. Imanian et al [14] engineered soft piezoresistive wearable conductors with TPMS-based architectures and evaluated the effects of pore shape on piezoresistivity in four different TPMS structures (i.e., Primitive, Diamond, Gyroid, and I-WP). Davoodi et al [15] fabricated durable and flexible 3D conductive sensors with interconnected TPMS structures, and found that different structural cell types could result in different gauge factors.…”
Section: Introductionmentioning
confidence: 99%
“…TPMS are mathematical structures that are known for their unique geometry and mechanical properties [15][16][17]. In recent years, 3D printing technology has been utilized to fabricate TPMS lattice structures using elastomeric materials such as TPU, silicone, and rubber [18,19]. One advantage of using 3D printing to fabricate TPMS lattice structures is its ability to create complex and highly customizable geometries.…”
Section: Introductionmentioning
confidence: 99%